Estratégias minimalistas na arquitetura dos anos 1980 e 1990 - Almeida, Décio Otoni de (2015)
In the 1980s and 1990s, part of the architectural scene was labeled as “minimalist”. The term, taken from the 1960s art movement known as Minimalism or Minimal Art, denoted a tendency to formal reduction in buildings of the time. Comparisons were made between aspects of Minimalism and architectural works, suggesting that architects have made use of art strategies. This research has considered four aspects of the topic – elementary form, materiality, uniform repetition and emptiness – as a starting point for the study of eight buildings, searching for similarities and differences between art and architecture approaches that may validate or not their association. The repercussion of Mies van der Rohe’s work in the 1980s and 1990s has also been evaluated. The 1986 reconstruction of the German Pavilion for the 1929 Barcelona International Exposition marks the return of the “less is more” dictum, which starts being considered once again by some of the architectural practices, after the postmodern critique of modernism in the previous two decades.